TINGKAT PENGETAHUAN ATLET GULAT KABUPATEN BANJAR TERHADAP PERATURAN PERTANDINGAN GAYA BEBAS - Tantawi, Ahmad; Anggara, Norma; Ahmad , Recky (Jurnal Pedagogik Olahraga, 2025)
This study aims to determine the extent of knowledge of wrestling athletes in Banjar Regency about freestyle match rules. This study uses a quantitative descriptive approach and 40 questionnaires are distributed as part of the data collection process. The population of the study was all active wrestling athletes in Banjar Regency. The method used was purposive sampling and the research sample was 12 athletes. The data analysis technique used in this study was a percentage approach. Based on the results of the study in Banjar Regency, it was in the "very high" category of 8.33% (1 athlete), the "high" category of 25% (3 athletes), "moderate" of 41.67% (5 athletes), "low" of 16.67% (2 athletes), "very low" of 8.33% (1 athlete) while based on the average value was 29.17. The conclusion of the results of the study is that the level of knowledge of wrestling athletes in Banjar Regency regarding freestyle match rules is included in the "moderate" category.